The Effect of Papaya—Lime Smoothie (Carica papaya L. & Citrus aurantiifolia) on Constipation Severity in Breast Cancer Patients Undergoing Chemotherapy - Agni Shinta Wardhani; Suhaema Suhaema; Ni Ketut Sri Sulendri; Aladhiana Cahyaningrum (http://dharmais.co.id/, 2026)
Background: Constipation is a common gastrointestinal complication among cancer patients undergoing chemotherapy, negatively affecting quality of life and treatment adherence. Non pharmacological interventions such as fruit-based dietary strategies may provide a safe and accessible alternative. This study aims to evaluate the effect of papaya—lime smoothie (Carica papaya L. & Citrus aurantiifolia) on constipation severity in breast cancer patients receiving chemotherapy.Methods: A quasi-experimental non-equivalent pretest—post-test control group design was conducted on 32 breast cancer patients at West Nusa Tenggara Provincial General Hospital. The intervention group (n=16) consumed 280 mL of papaya—lime smoothie daily for three days, while the control group (n=16) received standard care. Constipation severity was assessed using the constipation assessment scale (CAS). Statistical tests included the Wilcoxon signed-rank, the Mann-Whitney U, and the t-tests.Result: The intervention group showed a significant reduction in CAS scores from 10.38 ± 1.99 (moderate constipation) to 1.94 ± 1.69 (no constipation) (p < 0.001), while the control group decreased from 9.88 ± 1.99 to 5.19 ± 1.51 (mild constipation) (p < 0.001). Between-group differences were significant (Î”=8.44 ± 1.50 vs Î”=4.69 ± 2.27, p < 0.001).Conclusion: Daily consumption of papaya—lime smoothie effectively reduced constipation severity in breast cancer patients undergoing chemotherapy and may be considered as an alternative supporting non-pharmacologic therapy in cancer care.